2017
DOI: 10.12659/aot.902805
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Graft-Versus-Host Disease After Transplantation of Hematopoietic Stem Cells from Unrelated Donors in the China Marrow Donor Program

Abstract: BackgroundWe identified risk factors for acute and chronic graft-versus-host disease (aGVHD and cGVHD, respectively) in recipients after hematopoietic stem cell transplantation (HSCT) from unrelated donors in the China Marrow Donor Program (CMDP).Material/MethodsWe analyzed follow-up clinical information from 1824 patients who underwent HSCT between 2001 and 2010.ResultsThe incidence of aGVHD and cGVHD after transplantation was 49.29% and 27.3%, respectively. aGVHD incidence decreased as HLA matching increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…We observed that aGVHD after Chemo-DLI was not associated with the cGVHD after Chemo-DLI. It is somewhat to our surprise because aGVHD was 1 of the most important risk factors for the occurrence of cGVHD [44,45]. We suggested that patients who experienced aGVHD after Chemo-DLI should receive immunotherapies until the aGVHD was controlled.…”
Section: Discussionmentioning
confidence: 96%
“…We observed that aGVHD after Chemo-DLI was not associated with the cGVHD after Chemo-DLI. It is somewhat to our surprise because aGVHD was 1 of the most important risk factors for the occurrence of cGVHD [44,45]. We suggested that patients who experienced aGVHD after Chemo-DLI should receive immunotherapies until the aGVHD was controlled.…”
Section: Discussionmentioning
confidence: 96%
“…The pathophysiology of aGVHD is complex and involves several inflammatory cytokines, whose release starts during the conditioning regimen (irradiation and/or chemotherapy), leading to a pro-inflammatory environment that promotes T cell activation, proliferation, and differentiation against target organs (Schroeder et al, 2011). About 50% of patients with GVHD will die because of disease complications, and this is matched only by aGVHD's high incidence rate among patients who undergo alloHSCT (Barton-Burke et al, 2008;Yang et al, 2017). Although alloHSCT leads to a higher chance of developing aGVHD, it also provides a stronger graft-versus-tumor (GVT) reactivity, by which the new immune system recognizes and mediates the immunological eradication of reminiscent cancer cells (Noriega et al, 2015;van Bergen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…GVHD, a known complication of allogeneic HCT, was observed in higher proportion in the CSJ148-treated patients. The reason for the higher rate in CSJ148-treated patients is not clear, although these patients were older, and older age is a risk factor for acute GVHD (22)(23)(24)(25)(26). Other imbalances in baseline characteristics may have also contributed to the higher proportion of graft-versus-host disease observed in CSJ148-treated patients.…”
Section: Discussionmentioning
confidence: 99%